Prevalence of depressive symptoms and correlating variables among German elite athletes - Nixdorf, I.; Frank, R.; Hautzinger, M.; Beckmann, J. (Journal of Clinical Sport Psychology, 2013)
Depression among elite athletes is a topic of increasing interest, but empirical data are rare. The present study aimed to provide insight into the prevalence of depressive symptoms among German elite athletes and possible associated factors. In an online survey of 162 athletes, we explored depressive symptoms, chronic stress, coping strategies and stress-recovery stales. Results indicated an overall prevalence of 15% for depression among elite athletes (n = 99), and revealed higher levels of depressive symptoms among the individual athletes than the team athletes. Furthermore, correlation analyses showed a significant connection between high levels of depressive symptoms and high levels of chronic stress, negative coping strategies and negative stress-recovery slates. Results indicate that the prevalence for depressive symptoms in elite athletes is comparable to that in the general German population. Moreover, exploratory analyses provide first indications of factors associated with depressive symptoms.